Challenges of the new water policies for the XXI century : proceedings of the Seminar on Challenges of the New Water Policies for the 21st Century, 29-31 October 2002, Valencia, Spain /: proceedings of the Seminar on Challenges of the New Water Policies for the 21st Century, 29-31 October 2002, Valencia, Spain. (2014) - Unknown
No abstract available